Development of a reliability, availability and maintainability (RAM) simulation model for gas lift and gas injection system: article - Syed Muzafar, Shariffah Nur Syazreen; Ahmad Fuad, Fazril Irfan; Muhammad Iskandar (2018)
In the oil and gas industry, oil production will reduce over the time as oil fields become mature, causing depletion in reservoir pressure and less oil flow to the surface. When reservoir energy is insufficient to bring the oil flowing to the surface, it is essential to use an artificial lift as a primary oil recovery to maintain the reservoir pressure. After artificial lift have been applied to the reservoir, secondary recovery might be used as an initiative to increase the recovery of crude oil. Based on A significant failure occurred at a power plant in the USA in 1995 as a result of a turbine blading design fault. Surrounding auxiliary equipment was also damaged costing $11 million [1]. One of the reasons is due to the operating conditions inside gas turbines that can damage the blades through particulates adhering to the blades. Turbine blades are very sensitive, any damage can reduce mass flow and effective pressure ration. Therefore, it is crucial to identify which equipment/component in the system is the most critical and need to be paid attention.